استخذامات الطلبة الجامعيين للإذاعة المرئية - سعود, عبدالنور (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسةالى مدى استخدام طلبة الجامعات للإذاعة المرئية وقد توصلت الدراسة الى: -ان العديد المبحوثين دائما يتعرضون للإذاعة المرئية ويستعملون الاذاعة في الفترة المسائية -ان العديد المبحوثين يشاهدون الاذاعة المرئية لسبب فكري وثقافي بالإضافة الى أنهم تكسبهم الاذاعة المرئية خبرات جديدة -وجودعادات وانماط استخدام طلبة الجامعيين للإذاعة المرئية, بالإضافة الى وجود دوافع لاستخدام الاذاعة المرئية كذلك نجد لها دور فعال تقوم به بالنسبة للطلبة الجامعيين This study aims at the extent to which university students use visual radio. The study found: - Many respondents are always exposed to visual radio and use radio in the evening - Many respondents watch the visual radio for an intellectual and cultural reason, in addition to the fact that the visual radio gives them new experiences There are habits and patterns of university students’ use of visual radio, in addition to the presence of motives for using visual radio, we also find that it has an effective role to play for university students.
مذكرة ماستر إعلام و إتصال
Keywords: الاذاعة المرئية –الطلبة –مواقع التواصل الاجتماعي; visual radio - students - social networking sites